Q: What is the answer to -2a plus y?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2a + a = 3a

If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7

9a +8 -2a -3 -5a = 2a +5

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

Related questions

a + a + a - 2a = 3a - 2a = a

2a + a = 3a

If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7

9a +8 -2a -3 -5a = 2a +5

4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]

4a

What is the solution of -2a plus 3a plus 5b

2a + 3a = 5a

8b -2a

x + 2a

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b

5a + 3 + (2a - 2) + a= 5a + 3 + 2a - 2 + a= 8a + 1